THE NECESSITY TO REGULATE MEDICALLY ASSISTED PROCRETATION BY A LAW IN THE REPUBLIC OF LITHUANIA - Sušinskaitė, Nastė (Teisė, 2015)
The article focuses on the analysis of the problematics and the need to legally regulate technology of medically assisted procreation. In most European countries medically assited procreation is regulated by laws, some countries MAP’s procedure include in the list of services of compulsorary health insurance. Lithuania doesn’t have a law regulating assisted procreation. The greatest discussion arises when the laws of assisted procreation are enacted and applied on ways and methods which are going to be applied and their compatibility with ethics, moral principles and public interest. The article also focuses on projects of laws, which were submitted to the parliament of the Republic of Lithuania.